Big Data in Action for Government : Big Data Innovation in Public Services, Policy, and Engagement - World Bank (World Bank, Washington, DC, 2017)
Governments have an opportunity to harness big data solutions to improve productivity, performance and innovation in service delivery and policymaking processes. In developing countries, governments have an opportunity to adopt big data solutions and leapfrog traditional administrative approaches